Reconnecting Youth: Beyond Individualized Programs and Risks. (April 2021) - Myers, Randy; Goddard, Tim; Davidtz, Jennifer
Presently in the United States, cognitive behavioral approaches are thought to be one of the most effective ways to intervene in the lives of young people in trouble with the law. However, such individualized approaches to youth in trouble with the law, and the risk-based logics that accompany them, say some, often ignore the relationships that young people have with caregivers, as well as the broader social ecological, economic and political contexts within which those relationships develop. Once the individual change work is completed, young people must have productive roles and supportive relationships to return to, especially if we want youth justice practice to translate into justice for youth . Given that meaningful attachments with others serve as the primary context within which individuals learn to regulate emotions and behaviors, youth justice policy and practice ought to seek to repair the capacity to attach and relate –and broader social policy reforms must address the social and economic inequalities that make the adversity and harm that undermine that capacity more likely. In this article, we discuss the limitations of over-relying on skills-based therapies and examine how the neglect of social, material and relational contexts can undermine the meaning and effectiveness of youth justice interventions. Following this, we describe how a youth justice system that attends to relational needs and structural inequalities might better meet the needs of young people.